Body mass index (BMI) and obesity in Nigerians with schizophrenia (2021)
Background: Few Nigerian studies have examined BMI in people with schizophrenia. The aims of the present study were to assess the prevalence and distribution of obesity in Nigerians with schizophrenia and to examine the clinical correlates of BMI and obesity. Methods: A total of 207 people with schizophrenia met the inclusion criteria and were evaluated for BMI. The Positive and Negative Syndrome Scale (PANSS), Hamilton Depression Rating Scale (HDRS), Social and Occupational Functioning Assessment Scale (SOFAS) were rated for all participants. Anthropometric measures such as weight and height were taken using a standard protocol. Results: The prevalence of obesity was 12.6%. The non-obese participants were made up of underweight 24 (11.7%), normal weight 118 (57%) and overweight 38 (18.4%). Compared to non-obese participants, obese participants were older, more educated, more likely to be employed, had higher incomes, lower PANSS score (negative subscale), had fewer female participants, and better social and occupational functioning (p<0.05) BMI was positively correlated with age and monthly income. In the adjusted model, age, gender and education were independently associated with obesity while only age was associated with BMI. Conclusion: The present study suggests that unlike in high-income countries, obese patients with schizophrenia in Nigeria have better social and psychological functioning than non-obese patients.